Sdhd ablation promotes thyroid tumorigenesis by inducing a stem-like phenotype. Issue 11 (November 2017) - Ashtekar, Amruta; Huk, Danielle; Magner, Alexa; La Perle, Krista; Zhang, Xiaoli; Piruat, José I; López-Barneo, José; Jhiang, Sissy M; Kirschner, Lawrence S
Abstract : Mutations in genes encoding enzymes in the tricarboxylic acid cycle (TCA, also known as the Krebs cycle) have been implicated as causative genetic lesions in a number of human cancers, including renal cell cancers, glioblastomas and pheochromocytomas. In recent studies, missense mutations in the succinate dehydrogenase (SDH) complex have also been proposed to cause differentiated thyroid cancer. In order to gain mechanistic insight into this process, we generated mice lacking the SDH subunit D (Sdhd) in the thyroid. We report that these mice develop enlarged thyroid glands with follicle hypercellularity and increased proliferation. In vitro, human thyroid cell lines with knockdown of SDHD exhibit an enhanced migratory capability, despite no change in proliferative capacity. Interestingly, these cells acquire stem-like features which are also observed in the mouse tumors. The stem-like characteristics are reversed by α-ketoglutarate, suggesting that SDH-associated tumorigenesis results from dedifferentiation driven by an imbalance in cellular metabolites of the TCA cycle. The results of this study reveal a metabolic vulnerability for potential future treatment of SDH-associated neoplasia.